Building physics concept understanding and problem-solving ability in online learning through concept attainment model - Distrik, I Wayan; Setiawan, Wawan; Ertikanto, Chandra (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
This research aimed to build physics concept understanding and to problem-solve in online learning through the concept attainment learning model. This research employed a quasi-experimental method with a non-equivalent control group pretest-posttest design. The population was natural sciences students in grade XI of Public Islamic School 1 in Pringsewu, Lampung, Indonesia. The samples consisted of 35 grade XI students from class IPA 3 for the experimental group and 34 grade XI students from class IPA 2 for the control group. The concept understanding test consisted of ten problems referring to Anderson and Krotwall’s indicators. The problem-solving test consisted of five problems referring to problems developed by Savage and William. The test results of physics concept understanding and problem-solving ability were analyzed descriptively by grouping the data, calculating the n-gain, and interpreting the data. The difference in physics concept understanding and problem-solving between experimental and control classes were analyzed using an independent sample t-test. The result showed that the n-gains of physics concept understanding and problem-solving ability were in the high and moderate categories, respectively, for the experimental class and the moderate and moderate categories, respectively, for the control class. The independent sample t-test showed that conceptual understanding and problem-solving ability differed significantly between the experiment and control classrooms. This result indicated that the concept attainment model in online learning was better for building physics concept understanding and problem-solving ability for senior high school students than other conventional learning models.